The Representation of Gender in English Textbooks - Santika, Pelsi (UNIB Press, 2023)
Gender representation in English textbooks has been an interesting issue because teachers use textbooks to explain their lessons in school. However, this type of research is still done infrequently by researchers. The aims of this study are to identify similarities and differences in gender representation in parts of text, gender representation in visual, and gender roles in occupation in English textbooks for Grade Eight in Indonesia. Two English textbooks from different authors and publishers were selected for this study: Textbook 1 (When English Rings a Bell) and Textbook 2 (Interactive English 2). The first result reveals that in the components of the text, male representations are more detectable than female representations. The similarity between the two textbooks describes that male representations are more visible than female representations in conversation script and exercise. However, unlike textbook 2 which also have male domination in two other components, textbook 1 portrays female domination in course material and reading passage. The second result is that male representations are more appeared than female representations in both individual and group settings in both English textbooks. In individual, male characters have the highest proportion in textbook 1 while in textbook 2, male characters in the group have the highest proportion. The last result is that male roles in occupations are portrayed in a larger number of occupations than female roles in occupations for both English textbooks. In Textbook 1, males have 7 categories of occupation, while females have 3 kinds of job. In Textbook 2, male roles identify 10 types of job, while female roles mention 6 categories of occupation. It can be concluded that male characters are more represented than female characters in parts of the text, visual, and role in occupation for both English textbooks. This causes gender inequality between males and females.